The Effect of Metacognitive Awareness and Critical Thinking on Academic Success: A Structural Equation Model - Demir, Yılmaz (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This study examined the effects of children's metacognitive awareness, critical thinking tendencies, and demographic characteristics (gender and parents' education levels) on their academic achievement in the social studies course using a structural equation model. The study group comprises 854 secondary school students aged 10-13 who attended three secondary schools in the central district of Kilis province during the 2022-2023 academic year. Within the scope of the research, a hypothesized path diagram was developed using a structural equation model. As a result of the research, it was determined that children's gender, and mothers' and parents' education level had an indirect effect on their academic success in the social studies course, their metacognitive awareness had a direct and mediating effect, and their critical thinking tendencies had a direct, indirect and mediating effect. In addition, it was determined that children's gender and parental education level had direct and indirect effects on their metacognitive awareness, and only a direct effect on their critical thinking tendencies.